2018
DOI: 10.1109/tc.2018.2807429
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Rounding for HUB Floating-Point Addition

Abstract: Half-Unit-Biased (HUB) is an emerging format based on shifting the represented numbers by half Unit in the Last Place. This format simplifies two's complement and roundto-nearest operations by preventing any carry propagation. This saves power consumption, time and area. Taking into account that the IEEE floating-point standard uses an unbiased rounding as the default mode, this feature is also desirable for HUB approaches. In this paper, we study the unbiased rounding for HUB floating-point addition in both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…To obtain both of these metrics, we compared the results of all the arithmetics under study to the same algorithm computed using the GNU MPFR multiple-precision library with 128 fraction bits, which we use as our golden solution. We chose the MSE as a general accuracy metric and the MaxAbsE to also take into account the maximum error, which can be a critical value in certain applications [44], [45].…”
Section: Polybenchmentioning
confidence: 99%
“…To obtain both of these metrics, we compared the results of all the arithmetics under study to the same algorithm computed using the GNU MPFR multiple-precision library with 128 fraction bits, which we use as our golden solution. We chose the MSE as a general accuracy metric and the MaxAbsE to also take into account the maximum error, which can be a critical value in certain applications [44], [45].…”
Section: Polybenchmentioning
confidence: 99%
“…SDF interacts with calcium and phosphate ions and creates fluorohydroxyapatite [18][19][20]. On a parallel level, the use of diode laser (DL) seems to be an attractive fluoride replacement, since many studies reported that when laser is used alone or with fluoride, it may enhance the dental resistance to caries attack [21,22,23]. Diode laser enhances the resistance of enamel to acidic attack [14,15].…”
Section: Egyptianmentioning
confidence: 99%
“…Nonetheless, the value is still very low and enough for many applications. Unbiased rounding could also be implemented [21], but its study is out of scope.…”
Section: A Error Analysismentioning
confidence: 99%